Improving the Thermal Conductivity of Unsaturated Polyester by Adding Fillers - رامـي جـورج; رامـي منصور; بديعة داوود (Latakia University Journal -Engineering Sciences Series, 2022)
The research aims to study the possibility of improving the thermal conductivity of unsaturated polyester (UPR). To achieve this goal, different types of fillers were used, such as: (titanium oxide, calcium carbonate, black carbon and copper powder). The The thermal conductivity coefficient was measured using HTC Liner Heat Conduction device, after preparing the samples in the laboratory. The results of the tests showed that the best thermal conductivity value was that containing 6% calcium carbonate, 1.5% black carbon and 12% copper powder, and The thermal conductivity value has increased by 89% compared to the conductivity of pure UPR.